2011
DOI: 10.1016/j.tree.2011.03.023
|View full text |Cite
|
Sign up to set email alerts
|

A proposed unified framework for biological invasions

Abstract: There has been a dramatic growth in research on biological invasions over the past 20 years, but a mature understanding of the field has been hampered because invasion biologists concerned with different taxa and different environments have largely adopted different model frameworks for the invasion process, resulting in a confusing range of concepts, terms and definitions. In this review, we propose a unified framework for biological invasions that reconciles and integrates the key features of the most common… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
1,786
2
56

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 1,992 publications
(2,035 citation statements)
references
References 37 publications
18
1,786
2
56
Order By: Relevance
“…As a result, our overall knowledge about the mechanisms driving invasions is still patchy. Although a few treatments of both invasive plants and animals are available (Blackburn et al 2011), a general synthesis of invasion ecology is still missing (C2 in Table 3).…”
Section: Invasion Theory: Lack Of Synthesis and Imprecise Hypothesesmentioning
confidence: 99%
“…As a result, our overall knowledge about the mechanisms driving invasions is still patchy. Although a few treatments of both invasive plants and animals are available (Blackburn et al 2011), a general synthesis of invasion ecology is still missing (C2 in Table 3).…”
Section: Invasion Theory: Lack Of Synthesis and Imprecise Hypothesesmentioning
confidence: 99%
“…Evidence has accumulated that the most invasive species (following Blackburn et al 2011) are not necessarily the ones that have the greatest impacts (Ricciardi and Cohen 2007;Ricciardi et al 2013;Horáčková et al 2014), and often, action is needed for locally abundant species considered to be casual at the regional scale (Andreu et al 2009). This is further complicated by the fact that impacts are context dependent (Pyšek et al 2012;Hulme et al 2013, Simberloff et al 2013Kumschick et al 2015a;Vilà et al 2015), which calls for standardized tools to quantify and compare impacts among species, taxonomic groups, sites, and regions.…”
Section: Introductionmentioning
confidence: 99%
“…However, the difficulties associated with collecting empirical data from large species interaction networks call for theoretical approximations to address this issue. Several authors have suggested comprehensive theoretical frameworks for the study of invasions in a community context (Shea and Chesson, 2002;van Kleunen et al, 2010;Blackburn et al, 2011).…”
Section: Introductionmentioning
confidence: 99%